Reply to discussion of the paper "A multi-technique investigation of the nanoporosity of cement paste - Jennings, Hamlin M.; Thomas, Jeffrey J.; Gevrenov, Julia S.; Constantinides, Georgios; Ulm, Franz Josef (My University, 2007)
A reply to discussion of the paper written by Hamlin M. Jennings, Jeffrey J. Thomas, Julia S. Gevrenov, Georgios Constantinides, and Franz-Josef Ulm on 'a multi-technique investigation of the nanoporosity of cement paste' done by Beaudoin and Alizadeh is presented. The authors are correct in noting that the water sorption length change isotherms published by Feldman and Sereda in 1964 predate the work of Roper. However, Feldman and Sereda reported data for the first rewetting and second drying, whereas Roper was the first to report equilibrium length and weight change data during first drying. In the paper, specimens were equilibrated for a few weeks at each reported RH level during which both weight and length were monitored, and while true equilibrium was probably not reached the final rates of change were very low. The experimental data suggest that a stable mechanical packing of particles cannot be achieved with a porosity greater than δ50%.